2018
DOI: 10.2134/agronj2018.01.0025
|View full text |Cite
|
Sign up to set email alerts
|

Corn Era Hybrid Macronutrient and Dry Matter Accumulation in Plant Components

Abstract: As corn (Zea mays L.) hybrids change over time, and with increased use of different plant components for feed, bedding, and energy production, it is important to know macronutrient distribution within plants and how nutrient concentration and accumulation varies during plant development. This field study was conducted in 2007 and 2008 to evaluate dry matter (DM) biomass, macronutrient concentration, and macronutrient content in corn plant fractions (stalk, leaf, tassel, ear shoot, cob, and grain) across develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
25
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 31 publications
12
25
2
Order By: Relevance
“…The other sources listed in Table 4 used mean nutrient concentration values. One possible explanation for the new numbers being lower than the older values is that nutrient levels have decreased and yield levels have increased with newer corn hybrids (Woli et al, 2018). In addition, it is possible that older numbers were not based on many samples, or that, to make sure that these numbers would never underestimate actual removal; they were set at the high end of ranges of values found.…”
Section: Grain Survey Results and Implications For Managementmentioning
confidence: 99%
“…The other sources listed in Table 4 used mean nutrient concentration values. One possible explanation for the new numbers being lower than the older values is that nutrient levels have decreased and yield levels have increased with newer corn hybrids (Woli et al, 2018). In addition, it is possible that older numbers were not based on many samples, or that, to make sure that these numbers would never underestimate actual removal; they were set at the high end of ranges of values found.…”
Section: Grain Survey Results and Implications For Managementmentioning
confidence: 99%
“…Chen and coworkers found that a maize variety that stayed green absorbed more Mg and had lower N remobilization compared with the other studied types. Another study suggested that 34–36% of grain N, 58–68% of P and 43–51% of K were remobilized from the vegetative organs of the maize plant . The concentrations of grain N, P, K, Mn, and Zn can be improved by increasing their remobilization from the vegetative organs .…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that 34-36% of grain N, 58-68% of P and 43-51% of K were remobilized from the vegetative organs of the maize plant. 58 The concentrations of grain N, P, K, Mn, and Zn can be improved by increasing their remobilization from the vegetative organs. 32 The results of our field experiment indicated that Mg application significantly increased the total remobilization amounts, remobilization efficiencies and apparent contributions to the grain in stems and leaves.…”
Section: Effects Of Mg Application On the Distributions Of Mg In Thementioning
confidence: 99%
“…In corn, 25 to 82% of grain N is derived from the remobilization of vegetative N accumulated before silking (Ta and Weiland, 1992;Ma and Dwyer, 1998;Mi et al, 2003;Lemaire and Gastal, 2009;Chen et al, 2014). Woli et al (2018) reported 34 to 36% of grain N, 58 to 68% of P, and 43 to 51% of K remobilized from vegetative parts. In contrast, the nutrient contribution to grain from the remobilization of micronutrients such as Fe, Mn, Cu, and B was reported to be low (Karlen et al, 1988;Brown and Shelp, 1997;Bender et al, 2013).…”
mentioning
confidence: 99%